Integrating rotordynamic and electromagnetic dynamic models for flexible-rotor electrical machines - Kalita, Karuna (2007)
The magnetic field within electrical machines causes an interaction between the electrical and mechanical dynamics of the system. In the simplest cases, when the rotor mean position is central in the stator, the interaction manifests itself mainly as a negative stiffness between the rotor and the stator. When the rotor mean position is offset relative to the stator, then components of force arise whose frequency in the stationary frame is twice the electrical frequency of the supply.